Cover Picture: Cation Additive Enabled Rechargeable LiOH‐Based Lithium–Oxygen Batteries (Angew. Chem. Int. Ed. 51/2020). Issue 51 (12th November 2020) - Bi, Xuanxuan; Li, Matthew; Liu, Cong; Yuan, Yifei; Wang, Hao; Key, Baris; Wang, Rongyue; Shahbazian‐Yassar, Reza; Curtiss, Larry A.; Lu, Jun; Amine, Khalil
Abstract : Developing rechargeable lithium–oxygen batteries with reversible LiOH formation/decomposition is challenging. In their Communication on page 22978, J. Lu, K. Amine et al. report that a cation additive can tune the solvation environment of Li ions, resulting in a change in cell chemistry to form LiOH. LiOH is shown to be reversibly charged at low voltage, without the presence of redox mediators or catalysts.